Presentation of Complications of Chronic Liver Disease at a Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objectives: To see presentations of various complications of chronic liver disease at a tertiary care hospital. Study Design: Retrospective study Place and Duration of Study: This Study was conducted at Medical Unit 1, Nishtar Hospital, Multan for a period of 6 months from 01-01-2010 to 30-06-2010. Patients and Methods: Patients admitted at Medical Unit 1, Nishtar Hospital, Multan were included in the study. The medical record of these patients was checked. The data obtained were entered in SPSS-11 and analyzed. Results: A total number of 50 patients were studied, 30 (60%) were male and 20 (40%) were female. Age of the patients ranged from 36-58 years. Mean age of the patients was 45.39 ± 4.77 years. All the patients presented with fatigue, generalized weakness, oedema feet, anorexia and nausea. Twenty (40%) patients presented with jaundice. Abdominal distension was present in 42 (84%) patients. Twenty two (44%) patients were having altered consciousness. Twenty three (46%) patients presented with haemetemesis and 28 (56%) with malena. Low grade fever was present in 26 (52%) patients. Epistaxis was present in 2 (4%) patients. Previous history of jaundice was present in 40 (80%) patients and history of alcohol intake was present in 12 (24%) cases. On examination, all the patients were found emaciated with protuberant abdomen. Twenty (40%) were clinically jaundiced. Oedema feet was detected in 48 (96%) patients. Palmar erythema was present in 26 (52%). Hepatic flaps were present in 24 (48%) patients. Shifting dullness and fluid thrill was present in 46 (92%) patients and engorged paraumblical veins were present in 36 (72%) patients. Splenomegaly was seen in 36 (72%) patients. Laboratory investigations revealed raised serum bilirubin in 26 (52%) patients and level of bilirubin was 3-6 mg/100 ml in most of the cases. ALT levels were raised in 33 (66%) patients above the twice of the upper limit of the normal value. Serum alkaline phosphatase was raised only in 1(2%) of patients. Platelet count was below 70000 in 32 (64%) patients. Anti HCV and HBsAg were detected in 38 (76%) and 12 (24%) patients respectively. Prothrombin time was prolonged ≥5 seconds (than control) in 36 (72%) patients. Serum albumin was less than 3 g/100 ml in all cases. Abdominal ultrasonography revealed coarse echotexture with nodular liver in 46 (92%) patients. Ascites was detected in 48 (96%) patients. Two patients (4%) had hepatic mass. Upper GI endoscopy revealed esophageal varices in 33 (66%) patients, fundal varices in 12 (24%) patients, gastric ulceration in 17 (34%) patients and duodenal ulceration in 11 (22%) patients. Conclusion: Patients of chronic liver disease present in tertiary care hospital at a very late stage of the disease and most common presentations are ascites, hepatic encephalopathy, upper GI bleeding and low grade fever. Awareness may be created to motivate the patients to report to tertiary care hospital at an early stage, so that development of these complications can be managed at the very initial stage